Estudio de factibilidad para la creación de una empresa como agente de carga internacional para pequeños y medianos empresarios en el modo de transporte marítimo en el distrito de Buenaventura - Valle del Cauca. (2015)
Through the years, it has been proved that the port of Buenaventura is still leading foreign trade activity in Colombia. Not only for its infrastructure, but the actual circumstances of trade opening that allows it to have two ports, one road way in process of modernization and future port projects. These aspects are an opportunity for the foreign trade sector, where International Freight Agency (IFA) are in charge of moving cargo to consolidation and des consolidation as well as providing logistic and storage. The technical aspects of the business proposal for an IFA presents no problems regarding to fixed asset requirements and the knowledge on the topic of port logistics; the demand is due to the increase that foreign trade activity will have, because of the signing of different FTA and the urgent need to modernize the port infrastructure, the access routes and maritime access channels. It can be determined that regarding to organizational issues an IFA is able to become an integral way to fulfill its business plan fully considering the administrative and legal requirements necessary to comply with the legal part. Finally, the financial aspect presents a viability for investment, made under the parameters of costs, expenses and income over the initial investment. This makes the business idea into a viable alternative, as it is confirmed by three basic financial indicators that calculated: the VPN yielded a result of feasibility, the IRR showed a result of higher rate of return of profitability and the B / C ratio concluded that the investment has permanent liquidity during the five years projected.